2011
DOI: 10.1007/s10930-011-9367-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Galectin-1 from Human Platelets: Its Interaction with Actin

Abstract: Galectins are a family of animal lectins defined by their β-galactoside-binding specificity and a consensus sequence in their carbohydrate-recognition domain. Galectin-1 (Gal-1) is expressed as a non-covalently linked homodimer present in a variety of tissues. Here we describe its isolation from human platelets by a procedure involving ionic exchange chromatography and affinity chromatography on lactose-agarose. Platelet Gal-1 co-purifies with actin, forming an actin-Gal-1 complex which does no dissociate even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…They had also found that gal-7 was localized in the podosomes of these cells, indicating that gal-7 is involved in organization of the actin cytoskeleton. Such a role has been well documented for galectin-1, which binds to the actin cytoskeleton and participates in actin polymerization-depolymerization by modulating the activity of small GTPase [ 22 , 23 ]. Alternatively, release of gal-7 in the tumor microenvironment by EOC cells may favor establishment of a local immunosuppressive response by killing immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…They had also found that gal-7 was localized in the podosomes of these cells, indicating that gal-7 is involved in organization of the actin cytoskeleton. Such a role has been well documented for galectin-1, which binds to the actin cytoskeleton and participates in actin polymerization-depolymerization by modulating the activity of small GTPase [ 22 , 23 ]. Alternatively, release of gal-7 in the tumor microenvironment by EOC cells may favor establishment of a local immunosuppressive response by killing immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Gal-1 is expressed on the extracellular surface of human platelets [ 121 ]. Gonzalez et al reported that Gal-1 forms complexes with monomeric actin intracellularly and co-purifies with actin in human platelets [ 122 ]. ADP-induced platelet aggregation can be inhibited by lactose or anti-Gal-1 serum in vitro [ 121 ].…”
Section: Thrombosismentioning
confidence: 99%
“…Galectin-1 is expressed in different types of muscle tissues [ 98 ] and essential for muscle functioning due to its association with sarcomeric actin on I bands [ 99 ] and overall high binding affinity to cytoplasmic actin [ 100 ]. Many processes of muscle development are associated with elevated levels of galectin-1 leading to myoblast fusion, terminal differentiation, and muscle regeneration [ 24 , 76 , 77 , 101 ].…”
Section: Galectin-1mentioning
confidence: 99%